On Selected Mechanisms of Word Formation with Extralinguistic Implications in Mind: The Case of the English Lexical Field Medicine - Grzegorz A. KLEPARSKI; Oskar MOSIOR (Styles of Communication, 2020)
In the history of English various word formation processes have contributed to the development of medical vocabulary. The primary aim of the paper is to present the influence of selected word formation mechanisms on slang lexical items in the English lexical field MEDICINE. In particular, we shall mention several lexical items that can be found in medical slang. Also, we shall analyse such lexical items as roach, Bordeaux, FORD, and 45C which at first glance do not seem to be medicine-oriented. While analysing these lexical items, we shall observe what makes them creative, unique, insulting and/or unpleasant as well as puzzling and misleading for those who are unfamiliar with them. In addition, we shall try to determine plausible connections between their origin, history, and medical senses.